Nursing as a profession for woman - Havens, Gertrude Julia (My University, 1896)
Introduction: There is constant agitation in these times about women entering the professions, while a century ago it was thought of little and talked of less. There are many reasons for this agitation, and it is now generally acknowledged, that it is right, and not only right, but economic for her to do so. One of the first reasons is because she can then be self-supporting, and independent. Unhappy youthful marriages, and marriages just for a home will not take place when the women are capable of making homes for themselves, and so often attached to the term “old maid,” loses its sting when that same “old maid” can support herself and others by her earnings, and when the sting is lost there will not be so many girls rushing into marriage, simply to avoid being a “cipher” in humanity. A second reason is that there are, in the thickly populated countries, more women than men, and many of these men will remain single, so leaving many women dependent upon their own exertions for a home. What shall these women do?
Citation: Havens, Gertrude Julia. Nursing as a profession for woman. Senior thesis, Kansas State Agricultural College, 1896.
Morse Department of Special Collections
Keywords: Agitation; Women; Professions; Economy; Theses; Manuscripts (documents)